PERAN KOMISI PENYIARAN INDONESIA DALAM MENGAWASI PENYELENGGARAAN PENYIARAN PADA MASA PANDEMI COVID-19 - Ni Putu Noni Suharyanti; Kadek Endra Setiawan (Jurnal Aktual Justice, 2021)
In order to support the government in overcoming the Covid-19 outbreak, Komisi Penyiaran Indonesia (KPI) has issued several policies related to broadcasting, especially on television. This policy was taken considering that television is still the media with the most audience reach and has a high duplication power in society. Therefore, in every program broadcast to the public, adherence to health protocols is a must. Based on this, it is necessary to examine in depth the role of KPI in overseeing broadcasting and the synergy between Central and Regional KPIs in overseeing broadcasting during the Covid-19 pandemic. The results showed that the KPI in supervising broadcasting during the Covid-19 pandemic played an optimal role in regulating and supervising broadcast content by issuing policies to broadcast the socialization of prevention of the spread of Covid-19 either through Public Service Ads (ILM) or other programs by television and radio. In addition, KPI also issued KPI Decree (KKPI) Number 12 of 2020 concerning Support of Broadcasting Institutions in Efforts to Prevent and Overcome the Spread of Covid-19. Then to follow up on the Circular on news related to the Covid-19 Virus, the Central KPI along with Regional KPI throughout Indonesia conveyed and reminded all Broadcasting Institutions to remain guided by broadcasting rules in broadcasting institutions to convey useful and accountable information.